Analisa Performa Program dan Budget Pemerintah Desa Gianyar sebagai Implementasi Peraturan Pemerintah Nomor 47 Tahun 2015 - Bandiyah, Bandiyah; Wismayanti, Kadek Wiwin Dwi (Jurnal Politik Indonesia: Indonesian Political Science Review, 2017)
In order to implement Law No. 6 of 2014, which is implemented through Government Regulation No. 47 in 2015 on village administration. One form of implementation success is when the village is able to manage their finances well and its villages with programs defenseless villages and use value. Gianyar regency is one of regencies in Bali is one of its villages namely Batuan Village became a pilot in Indonesia in the financial management of funds of the village. However this is not enough to show that the performance of financial management have the tools and good execution. This study was conducted to see of information and knowledge about how the government's performance in particular village in Gianyar manage your finances as the village fund. The method used in conducting this study is qualitative analytical methods to test the comparability of financial statements village (assessment aimed at growth of revenue and expenditure of the village).